Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1995
DOI: 10.1111/j.1365-4362.1995.tb01560.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Evaluation of the Lupus Band Test in Discoid and Systemic Lupus Erythematosus

Abstract: The high negative predictive value of LBT in SLE suggests that it is valuable in excluding diseases clinically similar to SLE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 12 publications
0
24
0
Order By: Relevance
“…[1][2][3][4][5][6][7] For the demonstration of immunoreactant deposition in the skin, using other techniques apart from direct immunofluorescence (DIF) on fresh tissue and/or tissue fixed in physiologic fixative is not well established. However, in kidney biopsy specimens, performing immunohistochemical (IH) assessment of complement deposition on paraffinembedded tissue is of great diagnostic value.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7] For the demonstration of immunoreactant deposition in the skin, using other techniques apart from direct immunofluorescence (DIF) on fresh tissue and/or tissue fixed in physiologic fixative is not well established. However, in kidney biopsy specimens, performing immunohistochemical (IH) assessment of complement deposition on paraffinembedded tissue is of great diagnostic value.…”
mentioning
confidence: 99%
“…Therefore, skin biopsies were obtained in most patients several years after disease onset, during the remission phase of their renal disease. The sensitivity of the Lupus Band Test in SLE has been reported to be as high as 93%, with a specificity of 87% [26]. Other authors have reported a positivity rate of 58% in a group of 90 SLE patients, although 87% of those with renal involvement had positive skin immunofluorescence [21].…”
Section: Discussionmentioning
confidence: 96%
“…64 The high positivity of this test makes it the most sensitive for lupus, but it is not the most specific, since these antibodies may be detected in other autoimmune or infectious diseases or even in The presence of immunoglobulins in lupus lesions and in lesion-free skin from non-sun-exposed areas has shown a range of results. 9,54,56,57 Sugai et al, 10 analyzed 71 patients with DLE and found 66.2% positive lesions; they raise the possibility that in earlier studies patients with SCLE or SLE had been included, which would account for a higher incidence of positive results for direct immunofluorescence. Prystowsky et al, 9 in a group of 80 patients, assessed 17 DLE patients, and had positive DIF for lesioned skin in 77%, whereas in 31 patients in whom cutaneous fragments collected from normal, non-sunexposed areas, were analyzed, no deposit of immunoglobulin was found.…”
Section: Serologic Testsmentioning
confidence: 99%